Deliberate self-harm is associated with allelic variation in the tryptophan hydroxylase gene (TPH A779C), but not with polymorphisms in five other serotonergic genes - Pooley, E; Houston, K; Hawton, K; Harrison, P (Cambridge University Press, 2003)
Background. There is a heritable component to suicidal behaviour, encouraging the search for the associated risk alleles. Given the putative role of the 5-HT (5-hydroxytryptamine; serotonin) system in suicidal behaviour, serotonergic genes are leading candidates. In particular, several studies have reported an association with variants in the tryptophan hydroxylase (TPH) gene. Method. We studied six serotonergic gene polymorphisms in a well-characterized sample of 129 deliberate self-harm subjects and 329 comparison subjects. The polymorphisms were TPH (A779C), 5-HT transporter (5-HTT, LPR S/L), monoamine oxidase A (MAOA G941T), 5-HT1B receptor (HTR1B G861 C), 5-HT2A receptor (HTR2A T102C), and 5-HT2C receptor (HTR2C Cys23Ser). Genotyping was done using polymerase chain reaction (PCR)-based assays. The primary analyses compared allele and genotype frequencies between cases and controls. There were a limited number of planned secondary analyses within the deliberate self-harm group. Results. The TPH A779 allele was more common in deliberate self-harm subjects than in controls (OR 1.38, 95% CI 1.02-1.88; P=0.03). None of the other polymorphisms were associated with deliberate self-harm. Within the deliberate self-harm group there were no associations with impulsivity, suicide risk, lifetime history of depression, or family history of deliberate self-harm. Conclusions. Our data extend the evidence that allelic variation in the TPH gene is a risk factor for deliberate self-harm. No evidence was found to implicate the other polymorphisms.